Experimental Investigation of CPW Fed Fractal Array Antenna - Murad, N.A.; Esa, Mazlina (2003)
This paper experimentally investigates the performance of a set of simple two element coplanar waveguide (CPW) fed fractal array antennas. The design is based on the single square microstrip patch antenna, operating at 1.57s GHz. This is the frequency of operation of a Global Positioning Satellite system receiving antenna. The basic patch antenna undergoes the first and second iteration process to form the first and second iteration fractal structures. The array elements are equally spaced between their corresponding centres. Through experimental investigations, it was found that the fractal antenna array operates at lower frequency of operations compared to the basic two element square patch antenna. The second iteration fractal array antenna has the lowest operating frequency, indicating a much more compact radiating structure. However, the reflection bandwidth decreases.